THE RESEARCH OF IMPROVEMENT WAYS FOR PYROLYSIS GAS COOLING AND BLOWING PROCESSES IN PYROLYSIS GAS POWER STATIONS USING CONVENTIONAL TECHNICAL SOLUTIONS - Obodovskyi, Ivan; Morozov, Viacheslav (Problems of Friction and Wear, 2023)
The article is dedicated to describing the research of different ways, appliances and solutions for flammable gas supply, transportation and cooling, performed in terms of authors’ PhD theses, related to pyrolysis gas production and application for electric power production. The main idea of this research is the investigation of opportunities of application of modern simple generally used technological solutions on pyrolysis gas power plants for the above mentioned units design. The research is related to different ways of pyrolysis gas cooling and also to the ways of the gas supply from gas generator to the consumer. Another goal is to create a systematic approach to the automation of pyrolysis gas production and transportation onto future pyrolysis gas powered electric power plants.